Beneficial Farming Practices and Assistive Technologies for Veterans and Limited Resource Farmers - Paula E. Faulkner; Robert Cobb Jr.; Osei Yeboah; Shon Smith; Tamirrah Cox (European Scientific Journal, ESJ, 2023)
Farmers need support. Along with financial support, there is a need to receive knowledge, skills, and resources to address how to perform safe farming practices, including physical and mental health limitations. This study assessed participants’ knowledge and beliefs related to critical farming practices needed to live safe and sustainable lifestyles. Workshops were delivered face-to-face and online, covering a range of farming practice topics such as assistive technologies and mental health. Data was collected via online surveys. Results found that respondents needed more information on Farm Safety and Health, and many reported little energy and feelings of hopelessness. It was concluded that participants would benefit from more specialized training to be sustainable. Recommendations for future studies include more workshops and training programs based on education and demonstrations on how best to live healthy and safe lifestyles.